Rooted in purpose: Community attachment and lifestyle entrepreneurship in low-density territories - Martins, A.; Patuleia, M.; Dias, Á. (Tourism and Hospitality, 2025)
Lifestyle entrepreneurship has become a crucial phenomenon in tourism, especially in low-density rural territories where traditional business models struggle to sustain economic and social vitality. Understanding how lifestyle entrepreneurs combine personal values, community attachment, and territorial identity is essential to uncover how entrepreneurship can promote sustainable development and resilience in these fragile regions. This study investigates how lifestyle-based entrepreneurs in rural Portugal embed themselves in local contexts and contribute to community revitalisation through tourism. A qualitative multiple case study was conducted with three ventures located in the Planalto Mirandês region, using semi-structured interviews, document analysis, and field observations. Thematic analysis was applied to identify key patterns of motivation, community involvement, innovation, and challenges. The results show that lifestyle entrepreneurs are primarily driven by intrinsic motivations related to self-fulfilment and attachment to place rather than profit. Their engagement with the community varies from transactional collaborations to transformational partnerships, generating social, cultural, and environmental values. This study advances the literature by proposing a conceptual model that integrates individual, relational, and territorial dimensions of embedded entrepreneurship, revealing how authenticity and social purpose shape innovation in rural tourism. Practically, the findings provide guidance for policy makers, local authorities, and development agencies seeking to design support mechanisms that enhance the contribution of lifestyle entrepreneurs to sustainable rural regeneration.